An HEVC-based Screen Content Coding Scheme - Li, Bin; Xu, Jizheng (2015)
This document presents an efficient screen content coding scheme based on HEVC framework. The major techniques in the scheme includes hash-based large-scale block matching, dictionary mode, palette mode, adaptive color space coding, and several improvements to intra block copy mode. This scheme was submitted as our response to the joint Call for Proposals (CfP) for coding of screen content issued by ISO/IEC JCT1/SC29/WG11, i.e. MPEG and ITU-T Q6/16, i.e. VCEG. Compared with other coding schemes in response to the joint CfP, the proposed scheme shows clearly advantages - 1) It is the only one that shows less encoding time compared with the HEVC reference scheme; 2) it has the best lossless coding performance; 3) it is one of the two best performing schemes in terms of lossy coding. Compared with HM-13.0+RExt-6.0, which is the state-of-art screen content coding system when responding to the joint CfP, the proposed coding scheme for screen content achieves the average bit saving of 20.3% 26.4% for lossy coding. The average bit saving for losslss coding is 15.5% 23.7% for different coding structures.